Further insights into chemical characterization through GC–MS and evaluation for anticancer potential of Dracaena draco leaf and fruit extracts - Valente, Maria João (2021)
The present study reports for the first time the amino acid and fatty acid compositions and the antitumoral activity of aqueous extracts obtained from Dracaena draco L. leaf and fruit. Metabolite profiles were determined by gas chromatography-ion trap-mass spectrometry (GC-IT-MS), with several amino acids, palmitic, linolenic and stearic acid being identified in the leaf extract, and only proline, oleic and stearic acid in the fruit extract. The in vitro antiproliferative activities of the extracts were tested against human colon (Caco-2), kidney (A-498), and liver (HepG2) cancer cell lines. In addition, primary cultures of normal and cancerous renal cells derived from kidney cancer patients were treated with D. draco extracts (0-400 μg/mL). Antiproliferative and cytotoxic effects were determined by the MTT assay. D. draco extracts inhibited proliferation of human colon and renal tumor cells in vitro, whereas no or weak effect was observed in HepG2 cells. Compared to the fruit extract, D. draco leaf extract exhibited stronger antiproliferative activity against all cancer cells. Our results indicate that D. draco, particularly the leaf, may be useful as a cancer chemopreventive and/or chemotherapeutic agent for colon and kidney cancers.